AEG-1/MTDH: A central regulator of tumor progression, metabolic adaptation, and therapeutic resistance in gliomas - Suleiman Ibrahim Mohammad; Asokan Vasudevan; Mutaz Jamal Al-khreisat; Safa H. Radhie; Zukhra Yakhshieva; Ibrokhim Sapaev; Mirza R. Baig; Navin Kumar Tailor; Divya Singhal; Amr Ali Mohamed Abdelgawwad El-Sehrawy (Tissue and Cell, 2027)

MicroRNA–SIRT1 crosstalk in liver diseases: molecular regulation of metabolism, inflammation, and cell survival - Amr Ali Mohamed Abdelgawwad El-Sehrawy; Safa H. Radhie; Mirza R. Baig; Djaloliddin Mansurov; Rekha M. M.; Priya Priyadarshini Nayak; Neeraj Bainsal; Divya Singhal; Aseel Smerat; Mohammed Jawad Alnajar (Molecular Biology Reports, 2026)

Integrative approach for delineating structural variants using optical genome mapping and long-read genome sequencing - Usha R. Dutta; Kritika Ramgopal; N. Divya Bhanu; Uzair Ahmed; Rajitha Ponnala; Rajani Sirineni; S. Vasantha Rani; Ashwin Dalal (Molecular Biology Reports, 2026)

Intermittent fasting synergizes with GCN5 inhibition to suppress RBM5-AS1/GCN5/PGC-1α–driven Warburg metabolism in ovarian cancer - Gayathiri Gunasangkaran; Saradhadevi Muthukrishnan; Divya R.; Dhiva S.; Anjali K. Ravi; Vijaya Anand Arumugam; Marie Arockianathan Pushpam (Functional & Integrative Genomics, 2026)

Standardization of artificial inoculation technique for foot rot of finger millet caused by Sclerotium rolfsii and its validation using qPCR-based pathogen quantification - M. Bharath; H. R. Raveendra; Ravichandra; Mantesh Muttappagol; N. Sagar; Shadab M. Katib; Akash Bevanur; P. Yashwanth; Gutha Venkata Ramesh; Divya Bhandhari (Journal of Plant Pathology, 2026)

Plant-Mediated CuO Nanoparticles for Reactive Orange Dye Adsorption: Experimental study and Machine Learning-Assisted Optimization - S. Murugeshwari; Madhan Gunasekaran; B. Senthil Rathi; R. M. Saravana Kumar; J. Divya (Water, Air, & Soil Pollution, 2026)

Microsatellite Markers Unveil the Genetic Tapestry of Milkfish Chanos chanos (Fabricius, 1775) in Indian Aquatic Realms - Divya Merin Jose; P. R. Divya (Biochemical Genetics, 2026)

Pollinia storage and viability assessment in Decalepis arayalpathra - S. Gokul; R. K. Divya; Anup S. Deshpande; P. Ravichandran; K. Ravikumar; M. K. Janarthanam; P. E. Rajasekharan; Pradeep Kumar Vishwakarma (Palynology, 2026)

Multiscale attribution of atmospheric methane variability in China using satellite observations and interpretable machine learning - Divya Singh; Jinkai Luan; Hongzheng Zhu; Akshit Kumar; Ning-Xin Wang; Junming Wu; Giri R. Kattel; Zhi-Guo Yu (Journal of Environmental Management, 2026)

Intraspecific Variation of Edwardsiella anguillarum From Non‐Anguillid Fish From Varied Geographic Origins - Abigail R. Armwood; Divya Rose; Geoffrey C. Waldbieser; Ethan Woodyard; Bradley M. Richardson; Esteban Soto; Cynthia B. Stine; Cynthia C. Ware; Paola Barato; Alvin C. Camus; Matt J. Griffin (Journal of Fish Diseases, 2026)
Edwardsiella anguillarum is a gram‐negative bacterium, synonymous with previously described atypical, fish‐pathogenic Edwardsiella tarda . Originally described from eels in 2015, E. anguillarum is an important global fish pathogen, particularly in tilapia. This study describes intraspecific phenotypic and genotypic variability among 17 E. anguillarum isolates from non‐anguillid fish hosts and varied geographic origins. Isolates demonstrated similar biochemical characteristics, with slight variation in motility and hydrogen sulfide production. Genomic relatedness among isolates was analysed with repetitive extragenic palindromic sequence‐based PCR (rep‐PCR) and multilocus sequence analysis (MLSA). Rep‐PCR with the ERIC II primer set revealed two distinct genetic clusters, while amplification strategies utilising the GTG 5 , BOX or ERIC I&II primer sets yielded more uniform profiles. While rep‐PCR deemed the isolates largely clonal, MLSA schemes using reference genes from published Edwardsiella MLSA studies revealed E. anguillarum isolates formed five discrete phylogroups. A unique, ~91.5 kB plasmid was identified in Costa Rican and Colombian isolates, associated with conjugative and transposable elements, plasmid mobilisation, and adhesion; however, no plasmid mediated antibiotic resistance genes were identified. This study provides insight into genetic diversity among E. anguillarum isolates from different hosts and geographic regions, identifying an optimal MLSA scheme from previous reports applicable to E. anguillarum isolates.

A 27-year retrospective analysis of 24,633 cases reveals the spectrum of chromosomal abnormalities in Southern India and identifies a novel translocation disrupting EFCAB3 - Usha R. Dutta; Rajitha Ponnala; Kritika Ramgopal; Divya Bhanu Nalla; Uzair Ahmed; Vijay Kumar Sunke; Ashwin Dalal (The Nucleus, 2026)

Prebreeding using untapped rice genetic resources: linking the gap between biodiversity and crop improvement - Santhosh Venna; Divya Balakrishnan; P. K. Singh; B. Arun; Suneetha Kota; S. Amurutha Rao; Naresh Kumar Sahu; S.V. SaiPrasad; R. M. Sundaram (Journal of Crop Science and Biotechnology, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

A new sesquiterpene lactone isolated from Ainsliaea smithii and cytotoxic activity against the A549 cancer cell line - Kishan Singh; Kaveri R. Washimkar; Divya Kushwaha; Madhav Nilakanth Mugale; Kapil Dev (Natural Product Research, 2026)

Bridging process-based hydrology and deep learning: exploring hybrid MIKE NAM–LSTM techniques for accurate streamflow prediction in a humid tropical river basin in India - Divya Chandran; Haleema Wardah; N R Chithra (Journal of Earth System Science, 2026)

Biophysical basis and morphological traits conferring resistance to yellow stem borer, Scirpophaga incertulas (walker) in land races of rice (Oryza sativa L.) - Divya D. Mallesh; Vijaykumar Lingaraj; B. Shivanna; Reddy C. N. Lakshminarayana; M. S. Kitturmath; H. R. Raveendra; K. R. Ashoka (International Journal of Tropical Insect Science, 2026)

District-Level Groundnut Yield Prediction in Gujarat State Using Machine Learning and Remote Sensing Data - Drashti Nayakpara; Divya Prajapati; Kamal Pandey; N. R. Patel (Journal of the Indian Society of Remote Sensing, 2026)

Soil health indicator variability and management sensitivity across soils, bioregions, and agricultural systems - Katherine A. Dynarski; Ekundayo Adeleke; R. Louis Baumhardt; Joseph Burke; Tiffany Carter; Paul DeLaune; Huijie Gan; Julie Grossman; Josh Heitman; Divya Kandanool; Katie Lewis; Katherine Naasko; et al. (Agriculture, Ecosystems & Environment, 2026)

Animal models of multiple sclerosis: applications and future directions in disease research - Sujitha R.; Shajahan K.; Yogalakshmi R.; Velan R. N.; Khiren S.; Divya R; Monisha A. (Metabolic Brain Disease, 2026)

Design, integration, and evaluation of a dual-arm robotic system for high throughput sampling from potato tubers - L.G. Divyanth; Syed Usama Bin Sabir; Divya Rathore; Lav R. Khot; Chakradhar Mattupalli; Manoj Karkee (Computers and Electronics in Agriculture, 2026)

Stress Resilience in Tuber Crops: A Closer View on Genome Editing and Molecular Approaches - Pandian Rajendran; Krishnagowdu Saravanan; B. Jagadhesan; R. Ramesh; Divya Bharathi; Pavithra Suryakumar; Nitin Sharma; Yogesh Yele; Ashish Marate; Niranjan Prasad; N. D. Vinay; Palaiyur Nanjappan Sivalingam; et al. (Journal of Plant Growth Regulation, 2026)

Wild species Oryza rufipogon as a potential donor for development of interspecific backcross population in the background of Samba Mahsuri (BPT5204) and detection of yield enhancing QTLs - M. Sridhar; C. Gireesh; Divya Balakrishnan; M. Sujatha; M. S. Anantha; C. H. Raveendra; P. Senguttuvel; D. Srinivasa Chary; V. P. Bhadana; R. M. Sundaram (Plant Physiology Reports, 2025)

Unraveling allelic variations and population structure in wild species and cultivars of rice (Oryza spp.) for yield-related genes - Musku Sridhar; Divya Balakrishnan; M. S. Anantha; P. Senguttuvel; R. M. Sundaram; L. V. Subbarao; D. Aleena; Ch. Raveendra; S. Rathod; S. R. Chimmli; G. Padmavathi; M. Sujatha; et al. (Cereal Research Communications, 2025)

Novel Efficient Genome-Wide STR Panels for the Conservation of the Endemic Catfishes of Western Ghats: Critically Endangered Hemibagrus punctatus Jerdon (1849) and Vulnerable Horabagrus brachysoma (Günther, 1864) - P. R. Divya; Divya Merin Jose; Magdeline Christo; Charan Ravi; Uttam Kumar Sarkar (Biochemical Genetics, 2025)

Genetic Diversity and Population Structure Analysis in Avocado (Persea americana) Accessions of India - B. M. Muralidhara; T. Sakthivel; D. C. Lakshmana Reddy; G. Karunakaran; V. Venkatravanappa; Siddanna Savadi; Divya Vani Vaka; Ponnam Naresh; K. S. Shivashankara; R. Venugopalan; M. K. Honnabyraiah (Agricultural Research, 2025)

Multi-environmental and multi-trait evaluation of elite finger millet genotypes for blast resistance using GGE biplot and stability analysis - Farooqkhan; K.B. Palanna; Gutha Venkata Ramesh; Prasanna S. Koti; H.R. Raveendra; T.S.S.K. Patro; Divya Bhandhari; Gandikota Brahmani; Prahlad Netam; Sujatha Bhat; H.E. Patil; Shaik Abdul Salam; et al. (Physiological and Molecular Plant Pathology, 2025)

A case series of functional movement disorders in paediatric population-phenomenology and clinical characteristics - Ajith Cherian; Divya Kalikavil Puthanveedu; Amod R; Soumya Sundaram (Acta Neurologica Belgica, 2025)

Metabolic dysregulation and temporal dynamics of NF-κB-p65/NLRP3, TXNIP, endoplasmic reticulum and mitochondrial stress in silica-induced pulmonary fibrosis in rats - Kaveri R. Washimkar; Chirag Kulkarni; Manendra Singh Tomar; Shobhit Verma; Divya Bhatt; Smriti Verma; D.V. Siva Reddy; Baisakhi Moharana; Amit Misra; Dnyaneshwar U. Bawankule; Srikanta Kumar Rath; Naibedya Chattopadhyay; et al. (Journal of Hazardous Materials, 2025)

Harnessing inter-subspecific genetic variability for hybrid rice improvement: analysis of genetic diversity, heterosis, and combining ability - K. Sruthi; K. B. Eswari; Ch. Damodar Raju; M. Sheshu Madhav; A. Dhandapani; M. Bala Satya Sree; K. Srikrishna Latha; P. Koteswararao; M. Sadath Ali; Divya Balakrishnan; P. Senguttuvel; Revathi Ponnuswamy; et al. (Euphytica, 2025)

Deciphering mating type and population genetic landscape of Magnaporthe population adapted to millets and rice in blast hotspots of India - K. B. Palanna; Gutha Venkata Ramesh; Prasanna S. Koti; H. D. Vinaykumar; Divya Bhandhari; H. R. Raveendra; T. S. S. K. Patro; T. V. Krishna; T. E. Nagaraja; R. Madhusudhana; C. Tara Satyavathi (Archives of Microbiology, 2025)

Marker Assisted Introgression and Evaluation of Retinol Equivalent Carotenoid in the Elite Cultivars Background from Traditional Landrace ‘Kavuni’ - Suvarna Rani Chimmili; G. Subashini; M. Raveendran; C. R. Anandakumar; Jyothi Badri; Divya Balakrishnan; S. Robin (Agricultural Research, 2025)

Optimized biodiesel production from Java olive seeds using a novel magnetic nanobiocatalyst and advanced optimization techniques - L.R. Monisha Miriam; Ajith J. Kings; Jain B. Marshel; R. Edwin Raj; S. Indran; D. Divya (Biomass and Bioenergy, 2025)

Systematic revision of the genus Orchidasma Looss, 1900 and description of Orchidasma orchilobata n. sp. from the loggerhead Caretta caretta (L.) and Kemp’s ridley Lepidochelys kempii (Garman) turtles - Thomas G. Rosser; Aiden Meaux; Ethan T. Woodyard; Justin M. Stilwell; Bradley M. Richardson; Logan R. S. Robison; Jill B. Hudnall; Kaylin McNulty; Jonah A. Nguyen; Divya Rose; Debra Moore; Beth Peterman; et al. (Systematic Parasitology, 2025)

Treatment of Chlorinated Volatile Organic Compounds Using Different Bioreactor Systems: Microbial Communities and Pollutant Removal - Divya Baskaran; Shishir Kumar Behera; Biswanath Mahanty; Mansi Aliveli; Amira Elmanadely; Abubakar M. Bilyaminu; Anina James; Eldon R. Rene; Ravi Rajamanickam (Water, Air, & Soil Pollution, 2025)

Separating Historical Catches Among Pygmy Blue Whale Populations Using Recent Song Detections - Trevor A. Branch; Cole C. Monnahan; Emmanuelle C. Leroy; Fannie W. Shabangu; Ana Širović; Salvatore Cerchio; Suaad Al Harthi; Cherry Allison; Naysa Balcázar Cabrera; Dawn R. Barlow; Susannah V. Calderan; Michael C. Double; et al. (Marine Mammal Science, 2025)
In the Southern Hemisphere and northern Indian Ocean, there are at least five populations of pygmy blue whales, Balaenoptera musculus brevicauda , residing in the Northwest Indian Ocean (NWIO, Oman), central Indian Ocean (CIO, Sri Lanka), Southwest Indian Ocean (SWIO, Madagascar to Subantarctic), Southeast Indian Ocean (SEIO, Australia to Indonesia), and Southwest Pacific Ocean (SWPO, New Zealand). Each population produces a distinctive repeated song, but none have population assessments or reliable measures of historical whaling pressure. Here we created pygmy blue whale catch time series by removing Antarctic blue whale catches using length data and then fitting generalized additive models (based on latitude, longitude, and month) to contemporary song data (largely from 1995 to 2023) to allocate historical catches to the five populations. Most pygmy blue whale catches (97% of 12,207) were taken by Japanese and Soviet operations during 1959/1960 to 1971/1972, with the highest totals taken from the SWIO (6514), SEIO (2593), and CIO (2023), and lower catches from the NWIO (549) and SWPO (528). The resulting predicted annual catch assignments provide the first indication of the magnitude of whaling pressure on each population and are a key step toward assessing the status of these five pygmy blue whale populations.

Evaluation of Eclipta alba L. selections for higher biomass and bioactive compound - K. Hima Bindu; K. Keshav Rao; Shiva Kumar; B. Anil Kumar; R. M. Shalini; Priti Sonavane; K. S. Divya; S. Sujatha (Genetic Resources and Crop Evolution, 2025)

Influence of fibre ratio and chemical treatment on the properties of hybrid epoxy composites reinforced with areca and banana fibre - Subramanya Raghavendra; Chandra Shekar A; Manjunatha KN; Suresha S; Madhusudhana SV; Arun Kumar R; Prabhakara SS; Divya SN; Satish Kumar KB; Raveendra RS (Journal of the Indian Academy of Wood Science, 2025)

Effect of integrated disease management modules against major diseases (bacterial blight/root rot and downy mildew) of opium poppy - Shivam Singh; R. S. Mishra; S. K. Singh; M. K. Maurya; J. R. Yadav; Divya Singh; Abhishek Kumar; V. V. Raghuvanshi (Vegetos, 2025)

Recent developments in the design of functional derivatives of edaravone and exploration of their antioxidant activities - R. Divya Mohan; Naveen V. Kulkarni (Molecular Diversity, 2025)

Wild introgression lines of Oryza nivara as potential donor for yield and seedling vigour traits and mapping associated genomic regions - D. Sai Teja; Divya Balakrishnan; P. Magudeeswari; Sonali Kar; P. Arun Kumar; G. Pranay; R. Pushpa; Kalyani M. Barbadikar; L. V. Subba Rao; N. Sarla; S. V. SaiPrasad; R. M. Sundaram (Euphytica, 2025)

Food Security Based Marine Life Ecosystem for Polar Region Conditioning: Remote Sensing Analysis with Machine Learning Model - Ganduri Srikanth; Divya Nimma; R. V. S. Lalitha; Pradeep Jangir; N. V. Siva Kumari; Arpita (Remote Sensing in Earth Systems Sciences, 2025)

BRCAIndica: a resource for ACMG/AMP classified BRCA1 and BRCA2 variants - Aastha Vatsyayan; R. I. Anu; Prerika Mathur; Divya Uchil; Ashish Joshi; Aradhana Dwivedi; Bhawna Sirohi; Aju Mathew; Dileep Damodaran; Soumya Surath Panda; Spoorthy Kolluri; Shaji K. Ayillath; et al. (Familial Cancer, 2025)

Allometric scaling and carbon sequestration in agroforestry species of the Western Himalayas: a model-based approach - Megha VR; R. Kaushal; Sadikul Islam; Uday Mandal; Harsh Mehta; Rajkumar; J. M. S. Tomar; Anand Kumar Gupta; Anupam Barh; Vishwal Madhav P; Vibha Singhal; Rajiv Pandey; et al. (Environmental Monitoring and Assessment, 2025)

Predictive Performance of Ensemble Learning Boosting Techniques in Daily Streamflow Simulation - Divya Chandran; N. R. Chithra (Water Resources Management, 2025)

Plant diversity and microbial interaction on soil carbon stock in the tropical homegardens: a nature-based solution to climate change - Athulya Tom; V. Divya Vijayan; T. K. Kunhamu; S. Sandeep; K. Surendra Gopal; V. Jamaludheen; B. R. Vishnu (Agroforestry Systems, 2025)

A spatially explicit assessment of factors shaping attitudes toward African elephant conservation - Sarah L. Carroll; Susanne M. Vogel; Purity Nititi Taek; Clevers Tumuti; Divya Vasudev; Varun R. Goswami; Jake Wall; Stephen Mwiu; Robin S. Reid; Jonathan Salerno (Conservation Biology, 2025)
Conservation plans that explicitly account for the social landscape where people and wildlife co‐occur can yield more effective and equitable conservation practices and outcomes. Yet, social data remain underutilized, often because social data are treated as aspatial or are analyzed with approaches that do not quantify uncertainty or address bias in self‐reported data. We conducted a survey (questionnaires) of 177 households in a multiuse landscape in the Kenya–Tanzania borderlands. In a mixed‐methods approach, we used Bayesian hierarchical models to quantify and map local attitudes toward African elephant ( Loxodonta africana ) conservation while accounting for response bias and then combined inference from attitude models with thematic analysis of open‐ended responses and cointerpretation of results with local communities to gain deeper understanding of what explains attitudes of people living with wildlife. Model estimates showed that believing elephants have sociocultural value increased the probability of respondents holding positive attitudes toward elephant conservation in general (mean increase = 0.31 [95% credible interval, CrI, 0.02–0.67]), but experiencing negative impacts from any wildlife species lowered the probability of respondents holding a positive attitude toward local elephant conservation (mean decrease = −0.20 [95% CrI −0.42 to 0.03]). Qualitative data revealed that safety and well‐being concerns related to the perceived threats that elephants pose to human lives and livelihoods, and limited incentives to support conservation on community and private lands lowered positive local attitude probabilities and contributed to negative perceptions of human–elephant coexistence. Our spatially explicit modeling approach revealed fine‐scale variation in drivers of conservation attitudes that can inform targeted conservation planning. Our results suggest that approaches focused on sustaining existing sociocultural values and relationships with wildlife, investing in well‐being, and implementing species‐agnostic approaches to wildlife impact mitigation could improve conservation outcomes in shared landscapes.

Novel Ti/rGO@ZnCr LDH derived MMO for photocatalytic conversion of atmospheric elements and organic pollutants into valuable resources - Prabagar Jijoe Samuel; Tenzin Thinley; Divya Vinod; Hosakote Shankara Anusha; Hemanth Vikram P R; Gurupadayya B M; Kotermane Mallikarjunappa Anilkumar; Manickam Selvaraj; Mohammed A. Assiri; Harikaranahalli Puttaiah Shivaraju (Journal of Environmental Chemical Engineering, 2024)

Geospatial assessment of agroforestry land use systems using very high-resolution satellite images and artificial intelligence - Shivam Trivedi; P. V. Vinod; B. Chandrasekaran; M. K. Nagashree; S. Rama Subramoniam; V. B. Manjula; Amrita Singh; J. K. Mani; Arun S. Suryavanshi; Sushilkumar B. Rehpade; Akash Goyal; N. R. Shankar Ram; et al. (Agroforestry Systems, 2024)

Application of artificial intelligence tools in wastewater and waste gas treatment systems: Recent advances and prospects - Shishir Kumar Behera; S. Karthika; Biswanath Mahanty; Saroj K. Meher; Mohd. Zafar; Divya Baskaran; Ravi Rajamanickam; Raja Das; Kannan Pakshirajan; Abubakar M. Bilyaminu; Eldon R. Rene (Journal of Environmental Management, 2024)

Land use and altitudinal variability in biomass and carbon storage potential in mid-hill and sub-humid conditions of north-western Himalayas - Priyanka Rajput; D. R. Bhardwaj; Jatin Kumar; Saakshi; Prashant Sharma; Aalok Gulabrao Yewale; Divya Khatri (Environment, Development and Sustainability, 2024)

Female Collegiate Athletes’ Concussion Characteristics and Recovery Patterns: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Jaclyn B. Caccese; Reid A. Syrydiuk; Thomas A. Buckley; Sara P. D. Chrisman; James R. Clugston; James T. Eckner; Elsa Ermer; Carrie Esopenko; Divya Jain; Louise A. Kelly; Allyssa K. Memmini; et al. (Annals of Biomedical Engineering, 2024)

Multi-environment testing revealed the effect of yield genes on the grain yield stability in diverse rice germplasm - Aleena Dasari; Divya Balakrishnan; Santosha Rathod; P. V. R. Rao; Laksminarayana R. Vemireddy; C. N. Neeraja; S. Vanisri; K. N. Ranjith; R. M. Sundaram; Jyothi Badri (Cereal Research Communications, 2024)

Linkage mapping and quantitative trait loci detection for seedling vigor and grain size in advanced backcross introgression lines from wild accessions of Oryza nivara - P. Magudeeswari; Divya Balakrishnan; Yoshimichi Fukuta; Hiroki Saito; D. Saitheja; G. Pranay; R. Padmashree; Kalyani M Barbadikar; Jyothi Badri; P. Senguttuvel; K. Sruthi; D. Ladhalakshmi; et al. (Genetic Resources and Crop Evolution, 2024)

Morphological and molecular data establishes Clinostomum dolichorchum n. sp. (Digenea: Clinostomidae) in the great blue heron Ardea herodias L. and American bullfrog Rana catesbeiana Shaw - Jonah A. Nguyen; Ethan T. Woodyard; Chris T. McAllister; Susan V. Marcquenski; Divya Rose; Celene M. Slifka; Logan R. S. Robison; Matt J. Griffin; T. Graham Rosser (Systematic Parasitology, 2024)

Fine mapping of interspecific secondary CSSL populations revealed key regulators for grain weight at qTGW3.1 locus from Oryza nivara - Malathi Surapaneni; Divya Balakrishnan; Krishnamraju Addanki; Venkateswara Rao Yadavalli; Arun Prem Kumar; P. Prashanthi; R. M. Sundaram; Sarla Neelamraju (Physiology and Molecular Biology of Plants, 2024)

Linum usitatissimum mediated green synthesis of Cu3V2O8 nanoparticles and its photocatalytic activity studies - Divya R. Basavannavar; Kunal Mohan Mishra; Adheena Biju; E. Vinay kumar; J.R. Naveen Kumar; B.M. Praveen; G. Nagaraju (Environmental Nanotechnology, Monitoring & Management, 2024)

Enhanced Oral Bioavailability of Isoformononetin Through Nanoemulsion: Development, Optimization, and Characterization - Nazneen Sultana; Divya Chauhan; Pavan K. Yadav; Manish K. Chourasia; Jiaur R. Gayen (Journal of Pharmaceutical Innovation, 2024)

Analysis of Muscle Fatigue Progression Using Geometric Features of Surface Electromyography Signals and Explainable XGBoost Classifier - N. Punitha; K. Divya Bharathi; S. R. Manuskandan; P. A. Karthick (Journal of Medical and Biological Engineering, 2024)

Mapping for yield related traits in rice reveals major effect QTL qFLA1.1 from Oryza nivara increases flag leaf area - Haritha Guttikonda; Gowthami Chandu; Suchandranath Babu Munnam; Kavitha Beerelli; Divya Balakrishnan; R. Madhusudhana; Sarla Neelamraju (Euphytica, 2024)

Familial adult myoclonus epilepsy: a pragmatic approach - Ajith Cherian; K. P. Divya; A. R. Swathy Krishnan (Acta Neurologica Belgica, 2024)

Development of polymorphic microsatellite markers for genetic stock identification of green chromide, Etroplus suratensis using next generation sequencing technology - Magdeline Christo; Divya Merin Jose; P. R. Divya; M. U. Rekha; U. K. Sarkar (Conservation Genetics Resources, 2024)

Biometeorological analysis on the molecular incidence of babesiosis and ehrlichiosis in dogs - Y. Ajith; Sasi Adithya; Varuna P. Panicker; N. Athira; V. Beena; M. Saifudeen Safeer; P. Preena; A. R. Nisha; C. Divya; S. G. Sangeetha; C. G. Umesh; R. C. Sundararajan; et al. (Theoretical and Applied Climatology, 2024)

Flowering onset time is regulated by microRNA-mediated trehalose-6-phosphate signaling in Cajanus cajan L. under elevated CO2 - Divya K. Unnikrishnan; Rachapudi V. Sreeharsha; Shalini Mudalkar; Attipalli R. Reddy (Physiology and Molecular Biology of Plants, 2024)

Mapping QTLs for grain iron, zinc, and yield traits in advanced backcross inbred lines of Samba mahsuri (BPT5204)/Oryza rufipogon - Gowthami Chandu; Divya Balakrishnan; Suchandranath Babu Munnam; Satendra K. Mangrauthia; Durbha Sanjeeva Rao; C. N. Neeraja; R. M. Sundaram; Sarla Neelamraju (Journal of Plant Biochemistry and Biotechnology, 2024)

Low clouds over the subtropical Indian Ocean and sub-seasonal circulation associations with the Indian summer monsoon - T. Gokul; R. K. Vellore; D. C. Ayantika; V. Divya; R. Krishnan; M. J. K. Reji (Climate Dynamics, 2024)

Diversity of Indian rice cultivars and landraces for seedling vigour and their association for yield related traits - Sai Teja Dayala; Divya Balakrishnan; Sonali Kar; J. L. Ganguli; L. V. Subba Rao; R. M. Sundaram (Vegetos, 2024)

Sub-lethal but potentially devastating - The novel insecticide flupyradifurone impairs collective brood care in bumblebees - Liliana R. Fischer; Divya Ramesh; Anja Weidenmüller (Science of The Total Environment, 2023)

Assessment of Heavy Metals in Agroecosystems of the Cauvery Delta Region, South India Using a Focal Species: The Pavo cristatus - Manjula Menon; Rangaswamy Mohanraj; K. R. Divya; N. P. Mohammedali (Proceedings of the Zoological Society, 2023)

Identification and validation of blast resistance Pi1 gene in the derived mapping population of rice variety, NLR34449 through molecular markers - Dasari Aleena; V. Padma; G. Rekha; M. S. Prasad; M. S. Madhav; E. Punniakoti; T. Dilip; P. Sinha; M. Kousik; M. A. Das; M. Anila; Lal Ahmmed; et al. (Indian Phytopathology, 2023)

Toxicity prediction and analysis of flavonoid apigenin as a histone deacetylase inhibitor: an in-silico approach - N. Divya Rajaselvi; M. D. Jida; Devu B. Nair; S. Sujith; Nisaath Beegum; A. R. Nisha (In Silico Pharmacology, 2023)

Impact of prepubertal bovine ovarian tissue pre-freeze holding duration on follicle quality - Divya Deeleep Bhagat Amonkar; Vincenzo Genovese; Vincenza De Gregorio; Angela Travaglione; Shubhashree Uppangala; R. Vani Lakshmi; Guruprasad Kalthur; Roberto Gualtieri; Riccardo Talevi; Satish Kumar Adiga (Reproductive Biology, 2023)

Taxonomic study of Eteoryctis syngramma (Meyrick, 1914) (Lepidoptera: Gracillariidae) immature and adult - R. Divya; N. Chitra; V. Balasubramani; R. Arulprakash; A. Sankari (International Journal of Tropical Insect Science, 2023)

Evaluation of Thermostable Biomolecule Cocktail from Algal-associated Hot Water Spring Bacteria for Antibiofilm Activities - Mubassira K. Shaikh; Divya D. Patel; Shraddha C. Dobariya; Anoop R. Markande (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

Tropical agricultural wooded land uses support high site use of forest birds - Biang La Nam Syiem; Don A. Driscoll; Divya Vasudev; Varun R. Goswami (Biological Conservation, 2023)

Identifying sustainable coexistence potential by integrating willingness-to-coexist with habitat suitability assessments - Susanne Marieke Vogel; Divya Vasudev; Joseph O. Ogutu; Purity Taek; Emilio Berti; Varun R. Goswami; Michael Kaelo; Robert Buitenwerf; Michael Munk; Wang Li; Jake Wall; Desalegn Chala; et al. (Biological Conservation, 2023)

Therapeutics through glycobiology: an approach for targeted elimination of malaria - Mallya Divya; Sowmya R. Prabhu; Kapaettu Satyamoorthy; Abdul Vahab Saadi (Biologia, 2023)

Panmictic stock structure of milkfish (Chanos chanos, Forsskål 1775) from Indian waters determined using mtDNA marker - Divya Merin Jose; P. R. Divya; Kuldeep K. Lal (Journal of Genetics, 2022)

Impact of Bisphenol A on Structure and Function of Mitochondria: A Critical Review - Divyani Nayak; Divya Adiga; Nadeem G. Khan; Padmalatha S. Rai; Herman Sunil Dsouza; Sanjiban Chakrabarty; Natalie R. Gassman; Shama Prasada Kabekkodu (Reviews of Environmental Contamination and Toxicology, 2022)
Bisphenol A (BPA) is an industrial chemical used extensively to manufacture polycarbonate plastics and epoxy resins. Because of its estrogen-mimicking properties, BPA acts as an endocrine-disrupting chemical. It has gained attention due to its high chances of daily and constant human exposure, bioaccumulation, and the ability to cause cellular toxicities and diseases at extremely low doses. Several elegant studies have shown that BPA can exert cellular toxicities by interfering with the structure and function of mitochondria, leading to mitochondrial dysfunction. Exposure to BPA results in oxidative stress and alterations in mitochondrial DNA (mtDNA), mitochondrial biogenesis, bioenergetics, mitochondrial membrane potential (MMP) decline, mitophagy, and apoptosis. Accumulation of reactive oxygen species (ROS) in conjunction with oxidative damage may be responsible for causing BPA-mediated cellular toxicity. Thus, several reports have suggested using antioxidant treatment to mitigate the toxicological effects of BPA. The present literature review emphasizes the adverse effects of BPA on mitochondria, with a comprehensive note on the molecular aspects of the structural and functional alterations in mitochondria in response to BPA exposure. The review also confers the possible approaches to alleviate BPA-mediated oxidative damage and the existing knowledge gaps in this emerging area of research.

Activated Hollow and Solid Carbon Spheres for Enhanced Removal Efficiency of Pharmaceutical Pollutants and Heavy Metals in Water - Devika Laishram; Divya Kumar; Vishav Kant; Bhagirath Saini; Kiran P. Shejale; R. Krishnapriya; Vikash C. Janu; Rahul Singhal; Rakesh K. Sharma (Water, Air, & Soil Pollution, 2022)

CTV Based Sensor for the Rapid Detection of Nitro Toluene With Computational Studies and Molecular Modelling - Patrick F. Fernandes; Hinaly Bhasin; Priyanka Kashyap; Divya R. Mishra (Journal of Fluorescence, 2022)

Yield Estimation of Cassava Using SIMCAS Model Over the Major Cassava Growing Regions in India - Divya K. Lekshmanan; Raji Pushpalatha; V. S. Santhosh Mithra; S. Sunitha; James George; M. Velmurugan; P. Ashok; N. V. Mhasker; K. D. Desai; R. Shiny; Gangadharan Byju (Agricultural Research, 2022)

A review on degradation of organic dyes by using metal oxide semiconductors - Sapna Yadav; Kriti Shakya; Aarushi Gupta; Divya Singh; Anjana R. Chandran; Anjali Varayil Aanappalli; Kanika Goyal; Nutan Rani; Kalawati Saini (Environmental Science and Pollution Research, 2022)

Comparison of proton transfer paths to the QA and QB sites of the Rb. sphaeroides photosynthetic reaction centers - Rongmei Judy Wei; Yingying Zhang; Junjun Mao; Divya Kaur; Umesh Khaniya; M. R. Gunner (Photosynthesis Research, 2022)

Assessment of heterotic potential and combining ability of novel iso-cytoplasmic restorer lines derived from an elite rice hybrid, KRH-2, for the development of superior rice hybrids - Swapnil Ravindra Kulkarni; S M Balachandran; R A Fiyaz; Divya Balakrishnan; K Sruthi; K Ulaganathan; A S Hari Prasad; R M Sundaram (Euphytica, 2022)

The Origin and Clinical Relevance of Yoga Nidra - Seithikurippu R. Pandi-Perumal; David Warren Spence; Neena Srivastava; Divya Kanchibhotla; Kamakhya Kumar; Gaurav Saurabh Sharma; Ravi Gupta; Gitanjali Batmanabane (Sleep and Vigilance, 2022)

Genetic stock identification in Perna viridis (Linnaeus1758) from the Indian Peninsula by using microsatellite markers - P. R. Divya; Linu Joy; Sunitha Poulose; P. M. Elizabeth Jency; V. S. Basheer; A. Kathirvelpandian; Vindhya Mohindra; Kuldeep Kumar Lal (Molecular Biology Reports, 2022)

Gender differences in progressive supranuclear palsy - Rohan R. Mahale; Syam Krishnan; K. P. Divya; V. T. Jisha; Asha Kishore (Acta Neurologica Belgica, 2022)

CTV Based Sensor for the Detection of Ni2+ Ions With Real Sample Analysis Based on Mechanism of Fluorescence Along with Computational Insights - Patrick F. Fernandes; Divya R. Mishra (Journal of Fluorescence, 2022)

A Sensor for the Detection of Cr (III) and Fe (III) Ions Based on “Turn Off” Mechanism of Fluorescence with Computational Studies - Patrick F. Fernandes; Divya R. Mishra (Journal of Fluorescence, 2022)

An Image-Based Framework for Ocean Feature Detection and Analysis - Divya Banesh; Mark R. Petersen; James Ahrens; Terece L. Turton; Francesca Samsel; Joseph Schoonover; Bernd Hamann (Journal of Geovisualization and Spatial Analysis, 2021)

A comprehensive study on preparedness, impacts, response and recovery from tropical severe cyclonic storm ‘GAJA’: lessons for the future - S. Leo George; K. Balasubramani; Sulochana Shekhar; E. Venkatesham; K. Arun Prasad; Aakriti Grover; Dinabandhu Mahata; Ashish Kumar; V. V. Ashique; R. S. Libina; Divya Rajeswari Swaminathan; A. Balasundareshwaran; et al. (Journal of Coastal Conservation, 2021)

Occurrence of the supposedly endemic Australian azooxanthellate coral Astrangia woodsi Wells, 1955 in the eastern Arabian Sea - Divya Viswambharan; K. R. Sreenath; S. Jasmine; K. K. Joshi; C. R. Sreeraj; Smruthu Mohan; Prathibha Rohit (Marine Biodiversity, 2021)

Re-Description of Sillago malabarica, Silver Whiting from Southern Indian Waters - P. R. Divya; Rahul G. Kumar; Linu Joy; C. P. Rajool Shanis; V. S. Basheer; K. K. Lal (Thalassas: An International Journal of Marine Sciences, 2021)

Crop Simulation Models as Decision-Supporting Tools for Sustainable Potato Production: a Review - K. L. Divya; Priyank Hanuman Mhatre; E. P. Venkatasalam; R. Sudha (Potato Research, 2021)

Growth, seed yield and nutritional characteristics of pigeonpea grown under elevated CO2 atmosphere - Divya K. Unnikrishnan; Rachapudi V. Sreeharsha; Attipalli R. Reddy (Acta Physiologiae Plantarum, 2021)

Exploration of Heat Stress-Responsive Markers in Understanding Trait Associations in Wheat - P. B. Manjunatha; Nivedita Sinha; Hari Krishna; Divya Chauhan; Pawan Kumar; Ranjeet R. Kumar; Neelu Jain; P. K. Singh; G. P. Singh (Journal of Plant Biology, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Quinalphos Tolerant Endophytic Bacillus sp. Fcl1 and its Toxicity-Alleviating Effect in Vigna unguiculata - Silju Juby; Divya Choyikutty; A. R. Nayana; K. Jayachandran; E. K. Radhakrishnan (Current Microbiology, 2021)

Identification of potential Mpro inhibitors for the treatment of COVID-19 by using systematic virtual screening approach - Ashish M. Kanhed; Dushyant V. Patel; Divya M. Teli; Nirav R. Patel; Mahesh T. Chhabria; Mange Ram Yadav (Molecular Diversity, 2021)

Optical Clearing of Skeletal Muscle Bundles Engineered in 3-D Printed Templates - Nethika R. Ariyasinghe; Jeffrey W. Santoso; Divya Gupta; Mark J. Pincus; Paul R. August; Megan L. McCain (Annals of Biomedical Engineering, 2021)

Leaf blast disease in finger millet [Eleusine coracana (L.) Gaertn.] caused by Bipolaris sorokiniana Sacc.: a histopathological study - Pereira Preethi; M. S. Sharada; C. R. Divya (Journal of Plant Diseases and Protection, 2020)

Newborn screening and single nucleotide variation profiling of TSHR, TPO, TG and DUOX2 candidate genes for congenital hypothyroidism - Yedukondalu Kollati; Radha Rama Devi Akella; Shaik Mohammad Naushad; Divya Borkar; Maunika Thalla; Swapna Nagalingam; Lokesh Lingappa; Rajesh K. Patel; G. Bhanuprakash Reddy; Vijaya R. Dirisala (Molecular Biology Reports, 2020)

Population connectivity and genetic structure of Asian green mussel, Perna viridis along Indian waters assessed using mitochondrial markers - P. R. Divya; P. M. Elizabeth Jency; Linu Joy; A. Kathirvelpandian; Rajeev Kumar Singh; V. S. Basheer (Molecular Biology Reports, 2020)

Evaluation of genetic diversity of parental lines for development of heterotic groups in hybrid rice (Oryza sativa L.) - K. Sruthi; B. Divya; P. Senguttuvel; P. Revathi; K. B. Kemparaju; P. Koteswararao; R. M. Sundaram; Vikram Jeet Singh; E. Ranjith Kumar; Prolay Kumar Bhowmick; K. K. Vinod; S. Gopala Krishnan; et al. (Journal of Plant Biochemistry and Biotechnology, 2020)

A Bayesian hierarchical approach to quantifying stakeholder attitudes toward conservation in the presence of reporting error - Divya Vasudev; Varun R. Goswami (Conservation Biology, 2020)
Stakeholder support is vital for achieving conservation success, yet there are few reliable mechanisms to monitor stakeholder attitudes toward conservation. Approaches used to assess attitudes rarely account for bias arising from reporting error, which can lead to falsely reporting a positive attitude toward conservation (false‐positive error) or not reporting a positive attitude when the respondent has a positive attitude toward conservation (false‐negative error). Borrowing from developments in applied conservation science, we used a Bayesian hierarchical model to quantify stakeholder attitudes as the probability of having a positive attitude toward wildlife notionally (or in abstract terms) and at localized scales while accounting for reporting error. We compared estimates from our model, Likert scores, and naïve estimates (i.e., proportion of respondents reporting a positive attitude in at least 1 question that was only susceptible to false‐negative error) with true stakeholder attitudes through simulations. We then applied the model in a survey of tea estate staff on their attitudes toward Asian elephants ( Elephas maximus ) in the Kaziranga–Karbi Anglong landscape of northeast India. In simulations, Bayesian model estimates of stakeholder attitudes toward wildlife were less biased than naïve estimates or Likert scores. After accounting for reporting errors, we estimated the probability of having a positive attitude toward elephants notionally as 0.85 in the Kaziranga landscape, whereas the proportion of respondents who had positive attitudes toward elephants at a localized scale was 0.50. In comparison, without accounting for reporting errors, naïve estimates of proportions of respondents with positive attitudes toward elephants were 0.69 and 0.23 notionally and at local scales, respectively. False (positive and negative) reporting probabilities were consistently not 0 (0.22–0.68). Regular and reliable assessment of stakeholder attitudes–combined with inference on drivers of positive attitudes–can help assess the success of initiatives aimed at facilitating human behavioral change and inform conservation decision making.

Relative stability of the S2 isomers of the oxygen evolving complex of photosystem II - Divya Kaur; Witold Szejgis; Junjun Mao; Muhamed Amin; Krystle M. Reiss; Mikhail Askerka; Xiuhong Cai; Umesh Khaniya; Yingying Zhang; Gary W. Brudvig; Victor S. Batista; M. R. Gunner (Photosynthesis Research, 2019)

In silico prediction of short hairpin RNA and in vitro silencing of activin receptor type IIB in chicken embryo fibroblasts by RNA interference - P. Guru Vishnu; T. K. Bhattacharya; Bharat Bhushan; Pushpendra Kumar; R. N. Chatterjee; Chandan Paswan; K. Dushyanth; D. Divya; A. Rajendra Prasad (Molecular Biology Reports, 2019)

Deciphering demographic history and fine-scale population structure of cobia, Rachycentron canadum (Pisces: Rachycentridae) using microsatellite and mitochondrial markers - P. R. Divya; Joy Linu; C. Mohitha; A. Kathirvelpandian; P. Manoj; V. S. Basheer; A. Gopalakrishnan (Marine Biodiversity, 2019)

Identification and feld evaluation of female sex pheromone of leaf-eating caterpillar, Opisina arenosella (Lepidoptera: Oecophoridae) - K. R. M. Bhanu; D. R. Hall; R. V. Awalekar; M. Chandrashekharaiah; T. N. Divya; M. S. Prabhakara; K. P. Jayanth (International Journal of Tropical Insect Science, 2018)

Overfishing and Climate Drives Changes in Biology and Recruitment of the Indian Oil Sardine Sardinella longiceps in Southeastern Arabian Sea - Vasant Kripa; Kolliyil S. Mohamed; K. P. Said Koya; R. Jeyabaskaran; D. Prema; Shelton Padua; Somy Kuriakose; P. S. Anilkumar; Preetha G. Nair; T. V. Ambrose; A. M. Dhanya; K. S. Abhilash; et al. (Frontiers in Marine Science, 2018)

Molecular characterization and expression profiling of BMP 3 gene in broiler and layer chicken - Devara Divya; Tarun Kumar Bhattacharya; Manthani Gnana Prakash; R. N. Chatterjee; Renu Shukla; Pothana Boyina Guru Vishnu; Amirthalingam Vinoth; Kotha Dushyanth (Molecular Biology Reports, 2018)

An integrated geotechnical database and GIS for 3D subsurface modelling: Application to Chennai City, India - Divya Priya B.; G. R. Dodagoudar (Applied Geomatics, 2018)

Estimation of Cd, Pb and flame retardants in electric mosquito bat using EDXRF, ICP-OES, AAS and GC–MS - B. Divya; S. Harish; K. Ramaswamy; M. Kishorebabu; N. Raju; R. Govindaiah; U. Rambabu; N. R. Munirathnam (International Journal of Environmental Science and Technology, 2017)

Pancreatic Cancer: Current Status and Challenges - Amanda R. Muñoz; Divya Chakravarthy; Jingjing Gong; Glenn A. Halff; Rita Ghosh; Addanki P. Kumar (Current Pharmacology Reports, 2017)

Development and Characterization of SSR Markers to Study Genetic Diversity and Population Structure of Horsegram Germplasm (Macrotyloma uniflorum) - R. K. Chahota; Divya Shikha; Maneet Rana; Vikas Sharma; Akshay Nag; T. R. Sharma; J. C. Rana; Hideki Hirakawa; Sachiko Isobe (Plant Molecular Biology Reporter, 2017)

Microwave assisted synthesis, antimalarial screening and structure–activity-relationship exploration of some phenylthiazolyl-triazine derivatives against dihydrofolate reductase - Supriya Sahu; Surajit K. Ghosh; Anirban Ghoshal; Junmoni Kalita; Prashant Gahtori; Divya R. Bhattacharyya (Medicinal Chemistry Research, 2016)

Molecular understandings on ‘the never thirsty’ and apomictic Cenchrus grass - Divya P. Syamaladevi; S. S. Meena; R. P. Nagar (Biotechnology Letters, 2016)

PPIA rs6850: A > G single-nucleotide polymorphism is associated with raised plasma cyclophilin A levels in patients with coronary artery disease - A. Vinitha; V. Raman Kutty; A. Vivekanand; G. Reshmi; G. Divya; S. Sumi; K. R. Santosh; N. S. Pratapachandran; Mullassari S. Ajit; C. C. Kartha; Surya Ramachandran (Molecular and Cellular Biochemistry, 2016)

Characterization of microsatellite markers in silver pomfret, Pampus argenteus (Perciformes: Stromateidae) through cross-species amplification and population genetic applications - C. MOHITHA; LINU JOY; P. R. DIVYA; A. GOPALAKRISHNAN; V. S. BASHEER; MOHAMMED KOYA; J. K. JENA (Journal of Genetics, 2015)

Molecular phylogenetics of three species of the genus Rastrelliger using mitochondrial DNA markers - V. S. Basheer; C. Mohitha; N. Vineesh; P. R. Divya; A. Gopalakrishnan; J. K. Jena (Molecular Biology Reports, 2015)

Erratum to: Marker assisted backcross breeding approach to improve blast resistance in Indian rice (Oryza sativa) variety ADT43 - Balakrishnan Divya; S. Robin; R. Rabindran; N. Senthil; M. Raveendran; A. John Joel (Euphytica, 2014)

Marker assisted backcross breeding approach to improve blast resistance in Indian rice (Oryza sativa) variety ADT43 - Balakrishnan Divya; S. Robin; R. Rabindran; S. Senthil; M. Raveendran; A. John Joel (Euphytica, 2014)

Regulation of Gβγi-Dependent PLC-β3 Activity in Smooth Muscle: Inhibitory Phosphorylation of PLC-β3 by PKA and PKG and Stimulatory Phosphorylation of Gαi-GTPase-Activating Protein RGS2 by PKG - Ancy D. Nalli; Divya P. Kumar; Othman Al-Shboul; Sunila Mahavadi; John F. Kuemmerle; John R. Grider; Karnam S. Murthy (Cell Biochemistry and Biophysics, 2014)

Gene interactions and genetics of blast resistance and yield attributes in rice (Oryza sativa L.) - B. DIVYA; A. BISWAS; S. ROBIN; R. RABINDRAN; A. JOHN JOEL (Journal of Genetics, 2014)

The impact of microRNA expression on cellular proliferation - Divya Lenkala; Bonnie LaCroix; Eric R. Gamazon; Paul Geeleher; Hae Kyung Im; R. Stephanie Huang (Human Genetics, 2014)

Mitochondrial ATPase 6/8 genes reveal genetic divergence in the Coilia dussumieri (Valenciennes, 1848) populations of north east and northwest coasts of India - A. Kathirvelpandian; A. Gopalakrishnan; W. S. Lakra; Gopal Krishna; Rupam Sharma; P. R. Divya; Raj Kumar; J. K. Jena (Molecular Biology Reports, 2014)

Resistance reaction of gene introgressed lines against rice blast (Pyricularia oryzae) disease - B. Divya; S. Robin; R. Rabindran; H. Manjunath; P. Valarmathi; A. John Joel (Australasian Plant Pathology, 2014)

XIAP inhibitor and antiestrogen embelin abrogates metastasis and augments apoptosis in estrogen receptor positive human breast adenocarcinoma cell line MCF-7 - K. R. Sumalatha; G. Abiramasundari; G. K. Chetan; T. Divya; G. Sudhandiran; M. Sreepriya (Molecular Biology Reports, 2014)

Epigenetics, Drugs of Abuse, and the Retroviral Promoter - Jasmine Shirazi; Sonia Shah; Divya Sagar; Michael R. Nonnemacher; Brian Wigdahl; Zafar K. Khan; Pooja Jain (Journal of Neuroimmune Pharmacology, 2013)

Flavonoid as chemotaxonomic markers in endemic/endangered species of Rauvolfia from Southern Western Ghats of India: A preliminary study - V. Divya Nair; R. Panneerselvam; R. Gopi (Plant Biosystems, 2013)

Coastal hazard mapping in the Cuddalore region, South India - S. Saxena; R. Purvaja; G. Mary Divya Suganya; R. Ramesh (Natural Hazards, 2013)

Experimental study of the interspecific competition between two sibling marine herbivorous rotifers in relation to food availability and initial population density - S. P. Divya; K. Kathiresan; P. Asha; V. Sekar; R. Rajasekaran (Acta Oceanologica Sinica, 2012)

Fe3O4-PEI-RITC Magnetic Nanoparticles with Imaging and Gene Transfer Capability: Development of a Tool for Neural Cell Transplantation Therapies - Humphrey H. P. Yiu; Mark R. Pickard; Cristina I. Olariu; Stephen R. Williams; Divya M. Chari; Matthew J. Rosseinsky (Pharmaceutical Research, 2012)

Molecular characterization of eight Indian Snakehead species (Pisces: Perciformes Channidae) using RAPD markers - Ajaz Ali Bhat; M. A. Haniffa; P. R. Divya; A. Gopalakrishnan; M. James Milton; Raj Kumar; Bilal Ahmad Paray (Molecular Biology Reports, 2012)

Effect of triadimefon: a triazole fungicide on oxidative stress defense system and eugenol content in Ocimum tenuiflorum L. - V. Divya Nair; R. Gopi; M. Mohankumar; J. Kavina; R. Panneerselvam (Acta Physiologiae Plantarum, 2012)

IL-33 synergizes with IgE-dependent and IgE-independent agents to promote mast cell and basophil activation - Matthew R. Silver; Alexander Margulis; Nancy Wood; Samuel J. Goldman; Marion Kasaian; Divya Chaudhary (Inflammation Research, 2010)

Brewing trouble: coffee invasion in relation to edges and forest structure in tropical rainforest fragments of the Western Ghats, India - Atul Arvind Joshi; Divya Mudappa; T. R. Shankar Raman (Biological Invasions, 2009)

Detection of Helicobacter pylori using nested polymerase chain reaction in gastric biopsy samples - Divya Mahajan; Anju Jain; Varsha Singh; A. K. Jain; G. R. K. Rao; Gopal Nath (Indian Journal of Clinical Biochemistry, 2008)

The Effect of Magnetic Field Dependent Viscosity on Thermosolutal Convection in a Ferromagnetic Fluid Saturating a Porous Medium - Sunil; Divya; R. C. Sharma (Transport in Porous Media, 2005)